2000
DOI: 10.1097/00004770-200008000-00008
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytotoxicity of a New Epoxy Resin Root Canal Sealer

Abstract: The cytotoxic effects of a new epoxy resin-based root canal sealer (AH-plus), together with those of two other commonly used endodontic sealers (AH26 and zinc oxide-eugenol), have been studied in vitro on a culture of human gingival fibroblasts. Cytotoxicity was assessed by direct incubation of sealers' extracts with the cultured fibroblasts at different time intervals. Morphological and cytotoxic effects of the sealers were evaluated microscopically and spectrophotometrically using the neutral red cytotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
50
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 10 publications
11
50
0
5
Order By: Relevance
“…AH Plus, a new formulation of the epoxy resinbased sealer AH26, exhibited severe cytotoxicity immediately after mixing, but its cytotoxicity sharply decreased after 8h. These results were in accordance with the study by Azar et al 17) . Leyhausen et al 23) reported that AH Plus caused minor or no cytotoxic effect and no genotoxic effect with 24h set sealer.…”
Section: ⅳ Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…AH Plus, a new formulation of the epoxy resinbased sealer AH26, exhibited severe cytotoxicity immediately after mixing, but its cytotoxicity sharply decreased after 8h. These results were in accordance with the study by Azar et al 17) . Leyhausen et al 23) reported that AH Plus caused minor or no cytotoxic effect and no genotoxic effect with 24h set sealer.…”
Section: ⅳ Discussionsupporting
confidence: 94%
“…The cause of this long-lasting cytotoxicity may be related to unreactive eugenol or zinc ion remaining in the zinc oxide and eugenol mixture [16][17][18] . Similar results were obtained in the studies of ZOE by Others 17,18) . Sealapex also showed severe long-lasting cytotoxicity until the end of the observation periods after it initially showed moderate cytotoxicity.…”
Section: ⅳ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,18,24,25 Also, in accordance with Miletic et al 25 and Al-Hiyasat et al, 26 cytotoxicity was reduced after 7 days, while the present work also showed a decrease by 14, 21, and 28 days. In contrast, Azar et al, 27 using the neutral red assay, demonstrated that AH Plus induced significant cytotoxicity at 1 and 4 h, but no toxicity was detectable after 4 h. Huang et al 28 demonstrated that AH Plus at 24 h was cytotoxic to astrocytes in a dose-dependent manner. They showed that this sealer was also genotoxic, with an inhibitory dose (ID 50 ) of 0.04 mg/mL.…”
Section: Discussionmentioning
confidence: 96%
“…Epoxy resin-based sealers have been introduced in endodontic practice because of their favorable characteristics, such as adhesion to tooth structure, long working time, easey manipulation, and good sealing ability 14) . Several studies showed that polymerized resin-based sealers presented less cytotoxicity compared to zinc oxide-eugenol and calcium hydroxide-based sealers 15,16) . However, the cytotoxic effects of resinbased root canal sealers related to their radiopacity have not yet been studied.…”
Section: ⅰ Introductionmentioning
confidence: 99%